2015
DOI: 10.1007/s11695-015-1789-1
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery Provides a “Bridge to Transplant” for Morbidly Obese Patients with Advanced Heart Failure and May Obviate the Need for Transplantation

Abstract: Bariatric surgery can achieve successful weight loss in morbidly obese patients with advanced cardiac failure, enabling successful heart transplantation. In some patients, cardiac transplantation can be avoided through surgical weight loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 33 publications
2
27
1
Order By: Relevance
“…Improvements in Congestive Heart Failure (CHF) symptoms and Assessment of New York Heart Association (NYHA) functional class are observed 6–12 months after surgery , indicating that excessive weight loss has a positive effect on cardiac remodelling. These findings are supported by several case series investigating the effect of bariatric surgery on LVEF in patients with end‐stage heart failure and/or patients scheduled for heart transplantation .…”
Section: After Bariatric Surgerysupporting
confidence: 62%
See 1 more Smart Citation
“…Improvements in Congestive Heart Failure (CHF) symptoms and Assessment of New York Heart Association (NYHA) functional class are observed 6–12 months after surgery , indicating that excessive weight loss has a positive effect on cardiac remodelling. These findings are supported by several case series investigating the effect of bariatric surgery on LVEF in patients with end‐stage heart failure and/or patients scheduled for heart transplantation .…”
Section: After Bariatric Surgerysupporting
confidence: 62%
“…Strictly taken, the guidelines of the IFSO (64) do not consider cardiac pathology solely as an indication for bariatric surgery. In patients with (end-stage) heart failure, several case series have demonstrated the positive effect of weight loss (due to bariatric surgery) on LVEF and the NYHA functional class (of heart failure) (34,38,(60)(61)(62). Ristow et al (65) reported on two patients who no longer required heart transplantation after successful weight reduction and improvement of LVEF.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Patient series have suggested beneficial effects on cardiac function 7 and prognosis 14 of bariatric surgery in patients with heart failure, but other studies have shown an inverse association of BMI with mortality among people with heart failure. 15, 16 The present study only included people without heart failure at baseline and hence gives no implications for treatment of obese people with heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…In advanced heart failure patients, bariatric surgery was initially used for weight loss as a bridge to cardiac transplantation [4, 5]. Surprisingly, bariatric surgery significantly improved both symptoms of heart failure and cardiac function in 50% of patients [57].…”
Section: Introductionmentioning
confidence: 99%
“…In advanced heart failure patients, bariatric surgery was initially used for weight loss as a bridge to cardiac transplantation [4, 5]. Surprisingly, bariatric surgery significantly improved both symptoms of heart failure and cardiac function in 50% of patients [57]. Post-surgical cardiac changes include significant improvements in cardiac geometry and function including decreased hypertrophy and dilation with increased EF and improved relaxation [8].…”
Section: Introductionmentioning
confidence: 99%